Contribution of the Added Resistors to the Strength Endurance Test for Achievement a 1500-Meter Run for Youth Runners - Ali Awadd Aziz; Eman Abdulameer Zoon (Institute of Medico-legal Publications Pvt Ltd, 2021)
The importance of research is to find out which resistors added to the special strength endurance testcontribute to a greater percentage with the achievement of a 1500-meter run for young runners.As for the research problem, it is summarized and through the researchers’ observation and acquaintancewith many sources, research and studies that dealt with the added resistors in tests for athletics, especially thestrength endurance tests for the effectiveness of 1500 meters running, it was found that what was used testa distance of 500 meters with resistances rates (3%, 5%) %, 7%) of the runner’s mass to measure the forcetolerance of a 1500-meter run, and which resistors are most appropriate for this test will not be determined.The study also aimed at the percentage of the added resistors’ contribution to the strength endurance testfor accomplishing 1500-meter jogging for youth runners, to achieve the goal, the researchers used thedescriptive method of the survey method to suit it with the research problem, the research communityincluded a 1500-meter runner for the youth category, and the sample was deliberately chosen, their numberis (10) runners, which represent a percentage of (33.33%) of the original community.